Time-resolved terahertz spectroscopy of conjugated polymer/CdSe nanorod composites - Lam, Yeng Ming (2014)
We report ultrafast carrier dynamics in hybrid CdSe nanorod / poly(3-hexythiophene) (P3HT) bulk heterojunction films measured by time-resolved terahertz spectroscopy, and compare to the well studied P3HT/phenyl-C61-butyric acid methyl ester (PCBM) blend. Both films show an improved peak photoconductivity compared to P3HT alone, consistent with efficient charge transfer. The photoconductivity dynamics show fast, picosecond trapping or recombination in the hybrid blend while the all-organic film shows no such loss of mobile charge over ns time scales. The ac conductivity for all samples is well described by a Kramers-Kronig compatible Jonscher-type power law with exponent between 0.5 and 1 suggesting that interchain hopping in the polymer or between nanorods occurs at frequencies higher than 3 THz immediately after photoexcitation.